A Review: The Use of In Ovo Feeding in Various Types of Poultry - Wahyuni; R. Afnan; N. Ulupi; Daryatmo (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
In ovo feeding is one way to increase poultry productivity by providing additional nutrition during the incubation period and can increase embryo growth. Many implementations of in-ovo feeding techniques have been carried out on various types of poultry, but a summary of the use of in-ovo feeding on various types of poultry has never been reported, therefore this study was conducted. This review article aims to determine the use of in-ovo feeding in various types of poultry. This study was conducted based on literature studies by analyzing secondary data and synthesizing research from various data sources originating from nationally accredited journals and reputable international journals that discuss the use of in-ovo feeding in various types of poultry. The study shows that the implementations of in-ovo feeding for various types of poultry have been mostly applied to broiler chickens and native chickens, but only a few in geese, ducks, and quails. In-ovo feeding has several advantages for enhancing nutrition and health, including preserving normal physiological status and preventing disease, so that poultry productivity can be increased.